The Made-Up State : Technology, Trans Femininity, and Citizenship in Indonesia - Hegarty, Benjamin (Book collections on Project MUSE., 2022)
"A history of transgender femininity in New Order (1965-1998) Indonesia, contending that waria, one of Indonesia's trans feminine populations, have cultivated a distinctive way of captivating the affective, material, and spatial experiences of belonging to a modern "public" through their relationship to technology"--